2016
DOI: 10.1039/c5cc07318a
|View full text |Cite|
|
Sign up to set email alerts
|

Facilitated carbon dioxide reduction using a Zn(ii) complex

Abstract: Two new Zn(II) complexes have been prepared and evaluated for their capacity to activate and reduce CO2. The electrochemical properties of dichlorobis[diphenyl-(2-pyridyl)phosphine-κ(1)-N]zinc(II) [corrected]. and dichloro[diphenyl-(2-pyridyl)phosphine-κ(1)-N]zinc(II) 2 are compared using cyclic voltammetry. Electrochemical results indicate that 2 leads to a facilitated CO2 reduction to evolve CO at a glassy carbon electrode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 39 publications
2
28
0
2
Order By: Relevance
“…Initially, we limited electrochemical experiments to include only complexes persistent enough to reveal crystallographic evidence of CO 2 adduct formation, but eventually extended these experiments to various Zn complexes which demonstrated more fleeting CO 2 interactions via FT-IR. One of these complexes [Zn(2-pyPPh 2 ) 2 Cl 2 (py = pyridyl)] that exhibited a short-lived CO 2 interaction proved to be an effective and robust catalyst for the conversion of CO 2 to CO, [9] which is consistent with other reports that a weak interaction between the catalyst and CO 2 is actually a desirable attribute for catalytic CO 2 transformations [10]. For example, the compound seen in Fig.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Initially, we limited electrochemical experiments to include only complexes persistent enough to reveal crystallographic evidence of CO 2 adduct formation, but eventually extended these experiments to various Zn complexes which demonstrated more fleeting CO 2 interactions via FT-IR. One of these complexes [Zn(2-pyPPh 2 ) 2 Cl 2 (py = pyridyl)] that exhibited a short-lived CO 2 interaction proved to be an effective and robust catalyst for the conversion of CO 2 to CO, [9] which is consistent with other reports that a weak interaction between the catalyst and CO 2 is actually a desirable attribute for catalytic CO 2 transformations [10]. For example, the compound seen in Fig.…”
Section: Introductionsupporting
confidence: 77%
“…In another example, [9] our group synthesized a Zn complex ([Ph 2 Ppy] 2 ZnCl 2 , py = 2-pyridyl) which showed no evidence of CO 2 interaction via NMR, even when experiments were performed at 100 psig CO 2 and at -48…”
Section: Co 2 Reactivity Studiesmentioning
confidence: 99%
“… 34 Notably, a recent study highlighted an organometallic Zn complex that can activate CO 2 for electroreduction through Lewis acid–base interactions. 35 The exact role of the Zn center in our catalyst structure warrants further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Some other organic–ligand based complexes have also been investigated as molecular electrocatalysts. Donovan et al synthesized two new Zn(II) complexes with phosphine groups and evaluated their ability to reduce CO 2 to CO . Kang et al reported an iridium pincer dihydride electrocatalysts adopted to reduce CO 2 to formates (HCOO − ), exhibiting high efficiency, selectivity and turnover numbers (≈54200), of which mechanism is shown in Figure b.…”
Section: Electrocatalysts For Electrocatalytic Co2 Reductionmentioning
confidence: 99%